Etica, politica, socialismo. Un capitolo del caso italiano - Ferrari, Massimo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
In contemporary Italian political debate we are witness to an increasing oblivion of a proper tradition of thought that lively animated the scene before and immediately after the First World War. This paper aims at focusing the contribution that among others Rodolfo Mondolfo, Piero Gobetti, and Carlo Rosselli offered in order to rethink the bond between ethics, socialism, and political action. This topic, as the author suggests, remains even today highly relevant.